The Al-Mumtaz Textbook in Teaching Arabic to Non-Specialists for the Development of Language Skills - Leni Erliana; Maksudin Maksudin; Muhammad Jafar Shodiq; Agung Setiyawan; Abdul Munip; Nurhadi Nurhadi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme)
This study aims to describe the role of Al-Mumtaz Textbook in teaching Arabic to non-specialist (non-Arab) learners from philosophical, theoretical, and practical perspectives, and to analyze its contribution to the development of the four main language skills: listening, speaking, reading, and writing. The research employs a qualitative approach with a descriptive-analytical design. The primary data were obtained through documentation and content analysis of Al-Mumtaz Textbook, which is used in Arabic language instruction for non-native speakers. The population of this study includes the entire content of Al-Mumtaz Textbook, which comprises several volumes and is widely used in various educational institutions in Indonesia, particularly at the elementary and non-formal education levels. The sampling technique used was purposive sampling, focusing on the first and second volumes that beginners commonly use. The sample consists of sections of the book containing language skill exercises and their instructional presentation. Data was collected through documentation. Data analysis was conducted using a qualitative descriptive method, based on the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that Al-Mumtaz Textbook significantly contributes to the gradual and contextual development of students' language skills. Its communicative approach and real-life-based exercises have also proven effective in increasing students’ confidence in using Arabic. Therefore, this book is considered a valuable primary reference for Arabic language instruction for non-specialist learners at various educational levels.